Effects of corporate governance on banking performance of commercial banks in Bangladesh - Morshed, Niaz; Kabir, Sardar Md Humayun; Muhibullah, Md; Rafia, Afroz; Asuhaimi, Fadhilah Abdullah (Macrothink Institute, 2020)
Corporate governance is the system by which organizations are directed, monitored and controlled. It is an oversight mechanism to ensure the management team efficiently allocates the organizational resources, so as to protect the interest of shareholders and stakeholders. There is a need for good corporate governance practice to stabilize the performance of financial institutions. This study investigated the influence of corporate governance in banking performance. Panel data analysis has been conducted for the top nine public and private commercial banks operating in Bangladesh for a period of 2009 to 2017. Board size, structure of internal audit committee and capital adequacy ratio were being taken as independent variables to measure the effects of corporate governance whereas return on asset, return on equity and earnings per share were being taken as dimensions for measuring bank performance. Correlation and regression analysis techniques were being used to examine the relationships between corporate governance practices and bank performance. The results indicated that CAR has the greater impact on Bank performance. The information derived from this study can be valuable and will help to enhance the understanding of the governing bodies of financial institutions for accelerating banking performance.